ESPAÇO, INTERSECCIONALIDADES E VIVÊNCIA COTIDIANA GAY NA CIDADE DE PONTA GROSSA, PARANÁ - Hanke, William (2016)
This research of thought brings how the spaces can make the daily living of gay men in the city of Ponta Grossa – Paraná, between oppression situations to relief. To achievement this research, were interviewees eight people who self-identify as gay men, with ages between 19 to 33 years. For this, we use both the concept of space and intersectionality, relating them based on the daily life of people which are being discussed here. Moreover, the systematization of the dates that are presented was done from the semistructured interviews, which has been posted in a database of the free application suite for desktop, BrOffice. The research showed that spaces such as the home of the parents and the school have been or was spaces in their oppression of existences. It is the fact that the relationships that constitute them have been substantiated by hegemonic identities constructed. This trajectory of research also showed that public spaces that make their experiences to become of neutrality, according to the behaviors that are colluding to their normativities. Already spatiality church was represented by the majority of interviewees while a space of controversial intersection, this because the constitutions of their relations are contradictory, that is, at the same time oppression and relief. Finally, the relief areas were represented by the own home, house of a friends and the LGBT party scene. The results show that the relief spaces have relation with that what is built by the people themselves and their relations of affectivity. The results of this collective analysis showed that even people have different spatial experiences by sharing them certain identities they start to connect through of a process of solidarity for had also experienced relations of oppression or privilege in their lives. Thus, we understand that all the spaces that make up the daily living of gay men analyzed here, are spaces that have in their constitutions power relations, the result of identity hegemony, result of several power mechanisms, including the gender.